Deficiency of a Niemann-Pick, type C1-related protein in toxoplasma is associated with multiple lipidoses and increased pathogenicity. - Bao Lige; Julia D Romano; Veera Venkata Ratnam Bandaru; Karen Ehrenman; Jelena Levitskaya; Vera Sampels; Norman J Haughey; Isabelle Coppens (PLoS Pathogens, 2011)
Several proteins that play key roles in cholesterol synthesis, regulation, trafficking and signaling are united by sharing the phylogenetically conserved 'sterol-sensing domain' (SSD). The intracellular parasite Toxoplasma possesses at least one gene coding for a protein containing the canonical SSD. We investigated the role of this protein to provide information on lipid regulatory mechanisms in the parasite. The protein sequence predicts an uncharacterized Niemann-Pick, type C1-related protein (NPC1) with significant identity to human NPC1, and it contains many residues implicated in human NPC disease. We named this NPC1-related protein, TgNCR1. Mammalian NPC1 localizes to endo-lysosomes and promotes the movement of sterols and sphingolipids across the membranes of these organelles. Miscoding patient mutations in NPC1 cause overloading of these lipids in endo-lysosomes. TgNCR1, however, lacks endosomal targeting signals, and localizes to flattened vesicles beneath the plasma membrane of Toxoplasma. When expressed in mammalian NPC1 mutant cells and properly addressed to endo-lysosomes, TgNCR1 restores cholesterol and GM1 clearance from these organelles. To clarify the role of TgNCR1 in the parasite, we genetically disrupted NCR1; mutant parasites were viable. Quantitative lipidomic analyses on the ΔNCR1 strain reveal normal cholesterol levels but an overaccumulation of several species of cholesteryl esters, sphingomyelins and ceramides. ΔNCR1 parasites are also characterized by abundant storage lipid bodies and long membranous tubules derived from their parasitophorous vacuoles. Interestingly, these mutants can generate multiple daughters per single mother cell at high frequencies, allowing fast replication in vitro, and they are slightly more virulent in mice than the parental strain. These data suggest that the ΔNCR1 strain has lost the ability to control the intracellular levels of several lipids, which subsequently results in the stimulation of lipid storage, membrane biosynthesis and parasite division. Based on these observations, we ascribe a role for TgNCR1 in lipid homeostasis in Toxoplasma.